Taranto's long shadow? Cancer mortality is higher for people living closer to one of the most polluted city of Italy - Cazzolla Gatti, Roberto (Sustainability)
A national-scale study in Italy showed an incidence of cancer higher in the territories indicated as highly polluted compared to the regional average. One of them, the city of Taranto in Apulia (Italy), which is considered one of the most polluted cities in Europe, has numerous industrial activities that impact population health. We studied the epidemiological effects of a high level of pollution produced by the industrial area of Taranto in increasing the mortality rate for some specific cancer types in the city and towns of the two provinces located downwind. We analysed 10-year mortality rates for 15 major types of tumours reported among the residents of Taranto, of eight surrounding towns, randomly placed within an imaginary cone in the main wind direction from the vertex of the industrial zone of Taranto, and of the two related provinces (Bari and Taranto's metropolitan areas). Our results confirm our hypothesis that the mortality rate for some specific types of cancer is higher than the norm in the municipality of Taranto. We also found strong evidence that, for 12 out of 15 tumour types, mortality decreases with the distance of the other towns from Taranto's industrial site. However, we have reasons to believe that other local causes may be implicated in the excess of mortality in some specific municipalities besides the potential dispersal of pollutants from the industrial area of Taranto. The proximity to Taranto cannot, in fact, explain all the anomalies detected in some populations. It is likely that other site-specific sources of heavy pollution are playing a role in worsening the death toll of these towns and this must be taken into serious consideration by environmental policymakers and local authorities.